Synthesis, phase composition and modified microwave dielectric properties of Mg2+ substituted Zn2SiO4 ceramics with uniform microstructure. (6th September 2019) - Ye, Zejun; Li, Jie; Wang, Gang; Qi, Zhenfeng; Gan, Gongwen; Yang, Yan; Zhang, Huaiwu
Abstract: Zn2 SiO4 ceramics were synthesized by the traditional solid-state process. The effect of Mg 2+ substitution on sintering process, phase composition, morphology and microwave dielectric properties were investigated. Doped with different amounts of Mg 2+ ion, the sintering temperature can be decreased to 1250 °C from 1350 °C. X-ray diffraction (XRD) patterns showed that there were no second phase appeared. Scanning Electron Microscope (SEM) images proved that moderate substitution of Mg 2+ ion could make contribution to the grain compactness in (Zn1−x Mgx )2 SiO4 ceramics. The microwave dielectric properties of the ceramics strongly depended on the substitution content and sintering temperature. The ε r values were related to the density and Q × f values were affected by the grain growth. Remarkably, the (Zn0.6 Mg0.4 )2 SiO4 ceramics sintered at 1250 °C presented excellent microwave properties: ε r = 6.097, Q × f = 129, 991 GHz and τ f = −49.18 ppm °C −1 .